Biosynthesis, characterization, comparative and synergistic activity of silver nano particles from bacillus Species against human pathogens - J PREMKUMAR,; CHERUKULA SURYABABU MOUNIKA,; A. SAHAYA LOURDH JENIFA LANCY,; R J HEMALATHA,; T SUDHAKAR, (International Journal of Pharma and Bio Sciences, 2017)
Nanotechnology is useful in diagnostic techniques, drug delivery, sunscreens, antimicrobial bandage, and disinfectants. In the present investigate work synthesis of silver nanoparticles was prepared by biological method by reducing silver nitrate using the bacteria Bacillus species. The construction of nanoparticles was established by UV-visible spectroscopy with a maximum absorbance at 434nm, characteristic of silver nanoparticles. Further characterization of XRD and FESEM was used to determine the metallic character of AgNPs as well as morphological structure of AgNPs. The dimension of AgNPs is 41.13nm. The antimicrobial activity was done by disc diffusion method. Different concentrations of AgNPs was added to the plate and the concentration which gave maximum value is selected. Comparative analysis of synthesized AgNPs was done with water, AgNO3, extracted sample and AgNPs. Further synergetic activity was done to confirm the antimicrobial activity of AgNPs. AgNPs shows good antimicrobial activity against human pathogens so it can be used in drug delivery system.